2022
DOI: 10.21608/edj.2022.140331.2120
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Effect of Cysteamine and Its Combinations With Various Intracanal Medications Against Enterococcus Faecalis

Abstract: Background:The microbiological ecosystem is considered the main obstacle in endodontics. Therefore, canal disinfection became a great priority. Aim of the study:This study was established to assess cysteamine's antibacterial effect against E. Faecalis and compare the improvement effect to its combination with various intracanal medicaments. Methods and Materials:Cleaning and shaping were performed on human single-rooted teeth then inoculated by E. faecalis biofilm. Samples were divided randomly into three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Results of both cell viability %, which re ected the number of lived/metabolically active cells in a population, and IC50 which re ected the dose of the cytotoxic compound at which 50% viability on BHK broblast cells was achieved were in harmony as they showed that TAP Cysteamine combination had the lowest cytotoxicity level compared to other intracanal combinations followed by Cysteamine and the highest cytotoxicity was with Chlorhexidine Cysteamine combination and usage of CHX Cysteamine combination should be in lowest concentrations as described by Mirhadi et al (32) It was approved that cysteamine has an acceptable antibacterial effect and a good synergistic effect with other intracanal medications, especially with triple antibiotic paste which showed a higher antibacterial effect (7,37) . Our study found that the TAP Cysteamine combination the least cytotoxic effect compared to others.…”
Section: Discussionmentioning
confidence: 96%
“…Results of both cell viability %, which re ected the number of lived/metabolically active cells in a population, and IC50 which re ected the dose of the cytotoxic compound at which 50% viability on BHK broblast cells was achieved were in harmony as they showed that TAP Cysteamine combination had the lowest cytotoxicity level compared to other intracanal combinations followed by Cysteamine and the highest cytotoxicity was with Chlorhexidine Cysteamine combination and usage of CHX Cysteamine combination should be in lowest concentrations as described by Mirhadi et al (32) It was approved that cysteamine has an acceptable antibacterial effect and a good synergistic effect with other intracanal medications, especially with triple antibiotic paste which showed a higher antibacterial effect (7,37) . Our study found that the TAP Cysteamine combination the least cytotoxic effect compared to others.…”
Section: Discussionmentioning
confidence: 96%